Therapeutic Potential of 5-HT2C Receptor Ligands. (2010) - Jensen, Nanna H.; Cremers, Thomas I.; Sotty, Florence
Abstract : Serotonin 2C receptors are G protein-coupled receptors expressed by GABAergic, glutamatergic, and dopaminergic neurons. Anatomically, they are present in various brain regions, including cortical areas, hippocampus, ventral midbrain, striatum, nucleus accumbens, hypothalamus, and amygdala. A large body of evidence supports a critical role of serotonin 2C receptors in mediating the interaction between serotonergic and dopaminergic systems, which is at the basis of their proposed involvement in the regulation of mood, affective behavior, and memory. In addition, their expression in specific neuronal populations in the hypothalamus would be critical for their role in the regulation of feeding behavior. Modulation of these receptors has therefore been proposed to be of interest in the search for novel pharmacological strategies for the treatment of various pathological conditions, including schizophrenia and mood disorders, as well as obesity. More precisely, blockade of serotonin 2C receptors has been suggested to provide antidepressant and anxiolytic benefit, while stimulation of these receptors may offer therapeutic benefit for the treatment of psychotic symptoms in schizophrenia and obesity. In addition, modulation of serotonin 2C receptors may offer cognitive-enhancing potential, albeit still a matter of debate. In the present review, the most compelling evidence from the literature is presented and tentative hypotheses with respect to existing controversies are outlined.